ЭТНИЧНОСТЬ: СУЩНОСТЬ И СТРУКТУРА - Чернявская, Юлия (Acta Neophilologica, 2009)
The paper is devoted to essence of ethnicity and its structure. It is written from the point of view of the “soft constructivism”. Ethnicity is designed not by elites in the mobilization purposes, it is broad by masses in a daily life, from this research position. The structure of ethnicity includes such components as: ethnic borders, ethnonimes, myths, ethnic time and territory, stereotypes, expectations, roles, an ethnic image and three types of ethnic identity. Owing to such structure ethnicity is a dynamical phenomenon.